Centrality of Shame Memories and Psychopathology: The Mediator Effect of Self‐Criticism. (16th September 2013) - Pinto‐Gouveia, José; Castilho, Paula; Matos, Marcela; Xavier, Ana
<x xml:space="preserve">Abstract</x> Research has shown that the centrality of shame memories is related to psychopathological symptoms. However, little is known about the role of self‐criticism on this association. The current study explored a mediator model in which self‐criticism was hypothesized to mediate the relationship between centrality of shame memories and depressive symptoms, and between centrality of shame memories and paranoid beliefs. A battery of self‐report instruments measuring centrality of shame memory (CES), forms (FSCRS) and functions (FSCS) of self‐criticism, depressive symptoms (DASS‐42), and paranoid beliefs (GPS) was administered to 204 participants from the general community population. Results showed did centrality of shame memories played an important role in depressive symptoms and paranoid beliefs. Only in depression did measures of self‐criticism act as a mediator between centrality of shame and depressive symptomatology. These findings point to the distinct role that self‐criticism plays on the relationship between shame memories and depressive and paranoid symptoms, adding to current evolutionary approaches on these two psychopathological features.